Isostructural charge-transfer cocrystals based on triptycene end-capped quinoxalinophenanthrophenazine - Ueberricke, Lucas; Ghalami, Farhad; Zhang, Wen-Shan; Rao, Vaishnavi J.; Rominger, Frank; Schröder, Rasmus R.; Elstner, Marcus; Mastalerz, Michael (Crystal growth & design, 2021)
Charge transfer (CT) crystals of an electron donor and an acceptor have electronic properties that are different from the two pure components. Despite the great potential of such CT crystals have for organic electronics, the control of the spatial arrangement of donor and acceptor molecules in the cocrystals plays a crucial role for the charge transfer itself or, for example, for charge transport. In most cases, by changing e.g. the acceptor components, various cocrystals are accessible but in almost all cases with different packing motifs and thus crystallographic parameters. This makes a direct and systematic comparison of different donor-acceptor pairs difficult or even impossible. On the basis of a triptycene end-capped dimethoxy-quinoxalinophenanthrophenazine (QPP-OMe) as a donor with six small electron-deficient molecules as acceptors, an isostructural packing could be realized, where the QPP-OMe donor is forming voids with nearly the same orientation and size to enclathrate the acceptor molecules, as has been revealed by single-crystal X-ray diffraction. The CT complexes were studied spectroscopically, supported by density functional theory calculations.
Gesehen am 28.07.2021